EFFECTIVENESS OF MORPHON CARDS IN LEARNING ABOUT VARIOUS ORGANISMS - Balamurugan, M. (SCHOOL SCIENCE, 2025)
Morphon simply means animal, creature, structure, being, body, entity, person or plant. Morphon cards are thick white A4 sheets having a colour picture or diagram of an organism drawn by students without a heading or label. This morphon card is supported by the description cards with the corresponding organism, including their common name, Tamil name and scientific name with short description in Tamil about that organism. The objective of the study was to improve the level of ‘identification and description of organisms in science’ among the students of eighth grade by the application of morphon cards through post-test. In this study, single group pre-test and post-test experimental design was adopted. The sample used was the total strength of 18 students (7 boys and 11 girls) of class eighth studying through Tamil medium in Government Middle School, Theperumanallur village, Thiruvidaimarudur block, Thanjavur district, Tamil Nadu. The findings of the study showed that t-value for the scores on pre-test and post-test in identification and description of organism for eighth class students was determined to be 8.04, which is found to be significant at 0.01 level. Moreover, Cohen’s d effect size analysis between pre-test and post-test was estimated to be 1.895, which was found to be very large. There is the request by the investigator that science teachers must implement this modest strategy in their teaching-learning, which can be further useful in understanding biodiversity of the known and unknown areas